Recent progress in compact thermal models - Lasance, C.J.M. (Ninteenth Annual IEEE Semiconductor Thermal Measurement and Management Symposium, 2003, 2003)
The paper presents a number of recent developments in compact thermal modelling. A substantial part is devoted to a discussion on the accuracy of boundary-condition-independent (BCI) compact thermal models (CTMs) in practical situations. It has been repeatedly shown that high accuracy can be obtained when comparing CTMs to detailed model results. However, these results are usually generated using certain assumptions. The validity of these assumptions is the main subject of this paper. An important conclusion is that the 'traditionally' generated CTMs perform very well in 'real-life' environments. Other recent developments that are shortly reviewed are: progress in dynamic compact modelling, the possibility of parameterisation, experimental calibration, and standardisation of CTMs.